Whole body sensing dummy of the elderly to evaluate robotic devices for nursing care. (18th April 2021) - Ogata, Kunihiro; Matsumoto, Yoshio
ABSTRACT: Robotic devices for nursing care are expected to help caregivers work with the elderly. Some robotic devices assist in the physical transfer of the elderly, and these robots come in contact with large surfaces of the human body. The regions of the buttock and the back may be uncomfortable due to the surface material or motions of the robotic devices. Therefore, sensing devices simulating a human body were developed to quantify and evaluate the load of a human body objectively. This simulated buttock consists of simulated bone and soft tissues, which include muscle, fat and skin. These regions have multi-axis force sensors to enable the quantification of the load due to the robotic devices used for nursing care. On measuring the soft exterior, it was found that the stiffness of the buttock dummy was similar to the human buttock. The comfort of a robotic bed was measured using the simulated buttock, and it was found that the shear force increased due to the deformation of the robotic bed. Thus, it was proven that the simulated buttock was capable of measuring the load of the human body when being used with robotic devices for nursing care. GRAPHICAL ABSTRACT: